Determinants of clutch size and reproductive success in the pied flycatcher - Siikamäki, Pirkko (1995)
This thesis deals with the mechanisms that influence optimization of clutch size. The studies were mainly carried out with experiments in a population of the Pied Flycatcher (Ficedula hypoleuca) breeding in central Finland. The adjustment of clutch size was affected by habitat quality. Females that were forced to breed in a habitat of poorer quality than where they had initially settled, laid smaller clutches than control females. Seasonal decline in the clutch size seemed to be an adaptation to both the deteriorating food supplies and temporally changing tradeoff between resources allocated to breeding and maintenance of parents (i.e. moult). The trade-off documented here between the current reproduction and moult of parents is suggested to be a link between two successive breeding attempts and thus a mechanism causing costs of reproduction. Although females seem to adjust their clutches to correspond to the approximate number of young they can raise, the effect of unpredictable and varying weather on the growth and mortality of young weakens the ability of females to adjust the clutch at the egg-laying time. Consequently, during adverse conditions brood reduction is a strategy for adjusting the brood size to the level parents can rear. In all, studies of this thesis suggested that the most important factor influencing the optimization of clutch size in this species is the amount of food available to nestlings that largely depends on the habitat quality and the time of season. Additionally, the trade-offs between the current breeding attempt and future reproduction also mould the evolution of clutch size.